AFM dendritips functionalized with molecular probes specific to cell wall polysaccharides as a tool to investigate cell surface structure and organization - Marion Schiavone; Nathalie Sieczkowski; Mathieu Castex; Emmanuelle Trevisiol; Etienne Dague; Jean Marie François (The Cell Surface, 2019)
The yeast cell wall is composed of mannoproteins, β-1,3/β-1, 6-glucans and chitin. Each of these components has technological properties that are relevant for industrial and medical applications. To address issues related to cell wall structure and alteration in response to stress or conditioning processes, AFM dendritips were functionalized with biomolecules that are specific for each of the wall components, which was wheat germ agglutinin (WGA) for chitin, concanavalin A (ConA) for mannans and anti-β-1,3/anti-β-1,6-glucan antibodies for β-1,3/β-1,6-glucans. Binding specificity of these biomolecules were validated using penta-N-acetylchitopentaose, α-mannans, laminarin (short β-1,3-glucan chain) and gentiobiose (2 glucose units linked in β 1→6) immobilized on epoxy glass slides. Dynamic force spectroscopy was employed to obtain kinetic and thermodynamic information on the intermolecular interaction of the binary complexes using the model of Friddle-Noy-de Yoreo. Using this model, transition state distance xt, dissociate rate koff and the lowest force (feq) required to break the intermolecular bond of the complexes were approximated. These functionalized dendritips were then used to probe the yeast cell surface treated with a bacterial protease. As expected, this treatment, which removed the outer layer of the cell wall, gave accessibility to the inner layer composed of β-glucans. Likewise, bud scars were nicely localized using AFM dendritip bearing the WGA probe. To conclude, these functionalized AFM dendritips constitute a new toolbox that can be used to investigate cell surface structure and organization in response to a wide arrays of cultures and process conditions. Keywords: Cell surface, Cell wall, β-Glucan, Chitin, AFM dendrtips, Anti β-1, 3-glucan antibodies, Molecular interaction